Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist - Atahuachi, Margoth; van Der Bent, M. Leontien; Wood, John R.i.; Lewis, Gwilym P.; Hughes, Colin E. (Phytotaxa, 2016)
Three new species of Mimosa (Leguminosae, Mimosoideae) M. chiquitaniensis, M. chochisensis and M. rastrera, two of them endemic to Bolivia, and the third also occurring in Brazil, are described and an annotated species checklist for the genus in Bolivia is presented. This brings the tally of species of Mimosa recorded from Bolivia to 55 (plus five doubtful species to be confirmed), an increase of ca. 50% since the monographic account of the genus published just over 25 years ago.